Shrek the halls [videorecording (DVD)] - Trousdale, Gary; Bishop, Sean; Cullen, Theresa; Riling, Bill; Cheng, Teresa; Shay, Gina; Myers, Mike, 1963-; Murphy, Eddie, 1961-; Diaz, Cameron; Banderas, Antonio; Steig, William, 1907-2003 (Dreamworks Home Entertainment, 2008)
After promising Fiona and the kids a Christmas they will remember and with no clue how to plan anything for the holidays, Shrek is forced to take a crash course in the holiday. Just when he thinks he has everything for their quiet family Christmas just right, Donkey, Puss in Boots, Gingy and the rest of the gang decide to crash the party.